Erratum to: The prognostic ability of the STarT Back Tool was affected by episode duration (Eur Spine J, (2016), 10.1007/s00586-015-3915-0) - Morso, L.; Kongsted, A.; Hestbaek, L.; Kent, Peter (Springer, 2016)
Unfortunately, there is a mistake in the published version of Table 1. In the last row of the table, the numbers corresponding to the proportion of people in the STarT Back Tool risk subgroups High Risk and Low Risk had been swapped. When these numbers are correctly swapped back, they then correspond with the numbers presented in lines 10–20 of the results section. This misleading error was only in the table layout and did not affect the results or the conclusions of the paper (Table presented).